Annealing and Impurity Effects in Co Thin Films for MOL Contact and BEOL Metallization. Issue 1 (1st January 2019) - Kelly, J.; Kamineni, V.; Lin, X.; Pacquette, A.; Hopstaken, M.; Liang, Y.; Amanapu, H.; Peethala, B.; Jiang, L.; Demarest, J.; Shobha, H.; Raymond, M.; et al.
Abstract : PVD, CVD, and electrodeposited blanket Co films were studied using SEM, XRD, XPS, SIMS, open circuit wet etching in DHF, and linear sweep amperometry. All Co films exhibit (002) hexagonal close packed preferred orientation that is enhanced upon anneal, except for the PVD Co, whose texture is unchanged. Although as-deposited film resistivity varies significantly, post-anneal resistivity values for all films are similar (∼ 6–8 μΩ cm). As-deposited PVD Co and Co plated from an acidic sulfate chemistry are relatively pure, dissolve slowly in DHF, and show modest changes upon annealing. As-deposited CVD Co has high levels of impurities and correspondingly high DHF etch rates; annealing significantly reduces impurities and improves DHF etch resistance. Increased Co and reduced O at the surface is observed by XPS upon anneal for all films except for PVD Co. The role of Co oxidation in interconnect resistance and leakage behavior is assessed by employing different Co dielectric cap processes.